Effectiveness of Community Empowerment Programs Through Joint Venture Groups (KUBE) In Bulungan Regency, North Kalimantan - Amaliah, Muflihah Rizqy; Saiman, Saiman (Journal Research of Social Science, Economics, and Management, 2023)
The Joint Business Group (KUBE) is a social assistance program from the Ministry of Social Affairs of the Republic of Indonesia, specifically the Directorate General of Social Empowerment and Poverty Reduction. The KUBE program is expected to empower the poor and reduce poverty. The purpose of this study was to determine the effectiveness of the community empowerment program through the Joint Business Group (KUBE) and to determine the inhibiting factors in the community empowerment program through the Joint Business Group (KUBE) in Bulungan Regency, North Kalimantan. The theory used in this study is Budiani's theory of effectiveness which includes four indicators, namely the accuracy of program targets, program socialization, achievement of program objectives, and program monitoring. In this study, the researcher used a descriptive method with a qualitative research approach. The results of this study indicate that the effectiveness of the community empowerment program through the Joint Business Group (KUBE) in Bulungan Regency, North Kalimantan has not been running well. This can be proven by the non-fulfillment of the four indicators that serve as references and benchmarks to see the effectiveness of a program.